Teachers’ autonomous motivation and work engagement: The role of the principal’s democratic leadership style and psychological climate - L. A. Mokretsova; O. A. Sychev; A. M. Bespalov; M. S. Vlasov; M. M. Prudnikova (Образование и наука)
Introduction. The dependence of autonomous motivation of teachers on the principal’s leadership style was previously considered on the basis of the concept of transformational leadership by B. Bass, whereas its relationship with the styles described in the concept of K. Levin is understudied. The mediators of relations between leadership styles and teachers’ motivation are not sufficiently studied. According to the self-determination theory, such mediators can include psychological climate.Aim. The aim of the current research was to develop an integrative concept of leadership styles by K. Lewin and the theory of self-determination by E. Deci and R. Ryan model of dependence of teachers’ professional motivation and work engagement on the principal’s leadership styles. An additional task was to analyse the mediating role of the psychological climate of the school staff.Methodology and research methods. The correlational research was realised with the sample comprising 238 secondary school teachers in Biysk. The participants answered the Professional Motivation Questionnaire, Utrecht Work Engagement Scale, Style of Leadership Questionnaire and Group Atmosphere Scale. During processing of obtained data the authors used correlation analysis, t-tests for comparison of means and structural equation modelling.Results. The elaborated structural model demonstrates that the democratic leadership style of the school principal is positively related to the autonomous motivation of teachers directly and indirectly through the psychological climate. The principal’s liberal leadership style is inversely related to teachers’ work engagement. In terms of self-determination theory, these results reflect different opportunities to meet the basic psychological needs of employees in teams with different psychological climate and principal’s leadership style.Scientific novelty includes elaborated model describing the relationship of principals’ leadership styles according to K. Lewin’s typology with autonomous motivation and work engagement of teachers. The revealed effect of partial mediation of relations between democratic leadership style and autonomous motivation of teachers through psychological climate clarifies the ideas about the system of socio-psychological factors of professional motivation.Practical significance consists in usage of the results for improvement of psychological training of principals, optimisation of their leadership style for creating better psychological atmosphere and support for teachers’ productive motivation.